Analisis Pemanfaatan Sampah Organik Sebagai Media Perkembangbiakan Maggot - G. M. Saragih; Marhadi Marhadi; Peppy Herawati; Asih Suzana; Lisa Channi Sari (Jurnal Daur Lingkungan, 2023)
Organic waste as a medium for maggot breeding to produce maximum compost yields. The quality and quantity of fly larvae breeding media greatly affect the nutrient content of the body and the survival of the larvae at the metamorphosis stage. This research is an experimental research model with a completely randomized design (CRD) consisting of 1 treatment. The treatment is given using selected organic waste. Analysis of the data in this study in the form of a table of results of laboratory analysis of compost characteristics, namely pH, C-Organic, N-Total and C/N ratio and maggot weight. The results of the Soil Test Laboratory are seen in the pH with rice, fruit and vegetable media experiencing differences in pH with values of 5.15, 5.5, 5.95 and 6.4 (acidic) looks different from the initial pH, in this test the pH value shows the medium used is quite good for the composting process. Table 4.2 also shows the difference in values at the time of testing, it can be seen from the 4 variations in C-Organic that the highest value in vegetable and fruit waste media reached 13.05 %, but did not meet the quality standards for good C-Organic values. for composting. In the N-Total the highest value is in the 4th variation with a value of 26.3 with an N-Total quality standard of 30% so that from the 4 variations of the media it does not exceed the N-Total quality standard which will affect the maggot weight, in contrast to C/N which has the highest value is the 4th variation with a value of 20, with the quality standard the best value of the C/N ratio in the composting process is 25-40%, and it can be concluded that the value of the C/N ratio has not met the quality standard of the C/N ratio so that affect maggot breeding with a span of 20 days.